PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSET (ROA) PADA PT. MAYORA INDAH TBK PERIODE 2013 – 2023 - Hana Jessica, Gaby; Hermawan, Hengki (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect between Current Ratio and Debt to Equity Ratio on Return On Asset in PT. Mayora Indah Tbk for the 2013-2023 period. The research method used in this study is quantitative descriptive. This study uses secondary data sourced from PT Mayora Indah Tbk's financial report data, namely the 2013-2023 period. This data processing uses SPSS version 26. The analyses used in this study are statistical descriptive analysis, classical assumption test, multiple linear regression analysis, correlation coefficient test, determination coefficient test (R2), t test and f test. The results of the study show that the Current Ratio partially has an effect and is significant on Return On Asset with a value of sig. 0.031 > 0.05 and the calculated value of 2.616 > ttable 2.306 and partially the Debt to Equity Ratio has a negative and insignificant effect on Return On Asset with a sig. 0.347 < 0.005 and the tcount value -0.999 and the ttable value 2.306. The results of the simultaneous study of Current Ratio and Debt to Equity Ratio have no effect and are not significant on Return On Asset with a value of 0.081 > 0.05 and Fcal 3,500 < Ftable 4.46. Meanwhile, the results of the R2 determination coefficient test show an R-Square value of 0.467, which means that together the Current Ratio and Debt to Equity Ratio to Return On Asset contribute by 46.7% while 53.3% is influenced by other variables that are not studied in this study. The results of the study on the R number of 0.683 are in the efficient interval between 0.800 - 1000, so it can be concluded that the relationship between variables is included in the strong category.